Analgesic use and risk of renal cell carcinoma: A case‐control, cohort and meta‐analytic assessment. Issue 3 (9th April 2016) - Karami, Sara; Daughtery, Sarah E.; Schwartz, Kendra; Davis, Faith G.; Ruterbusch, Julie J.; Wacholder, Sholom; Graubard, Barry I.; Berndt, Sonja I.; Hofmann, Jonathan N.; Purdue, Mark P.; Moore, Lee E.; Colt, Joanne S.
Abstract : Analgesics are the most commonly consumed drugs worldwide. Evidence that analgesics increase kidney cancer risk has been mixed. We investigated the association between renal cell carcinoma (RCC) and analgesic use in a large population‐based case‐control study and a post‐trial observational cohort study. Findings were used to update a recent meta‐analytic review. We analyzed data from 1, 217 RCC cases and 1, 235 controls in the US Kidney Cancer Study and 98, 807 participants in the US Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO: n = 137 RCCs). Self‐reported acetaminophen, aspirin and nonsteroid anti‐inflammatory drug (NSAID) use and duration information was assessed in relation to RCC. For the US Kidney Cancer Study, we calculated odds ratios (ORs) and 95% confidence intervals (CIs) using unconditional logistic regression. For PLCO, we computed hazard ratios (HRs) and 95%CIs using Cox regression. Among case‐control participants, RCC risk was associated with over‐the‐counter acetaminophen use (OR = 1.35, 95%CI = 1.01–1.83). There was a positive trend with increasing duration ( p ‐trend = 0.01), with a two‐fold risk for use ≥10 years (OR = 2.01, 95%CI = 1.30–3.12). No association with prescription acetaminophen use was detected. In PLCO, acetaminophen use was also associated with increased RCC risk (HR = 1.68, 95%CI = 1.19‐2.39), although elevated risk was absent among the few long‐term users. No association with RCC risk was detected for aspirin or NSAIDs use in either study. An association between acetaminophen use and kidney cancer was supported by meta‐analytic cohort ( n = 4; summary relative risk = 1.34; 95%CI = 1.13–1.59; p‐ heterogeneity = 0.40) and case‐control ( n = 9, summary OR = 1.20; 95%CI = 1.01‐1.42; p‐ heterogeneity = 0.05) findings. In brief, acetaminophen use may increase the risk of developing RCC. Abstract : What's new? Analgesics, taken for pain relief or to reduce fever, are the most commonly consumed medications in the world. Could these drugs influence the risk of kidney cancer? This paper examined the effect of aspirin, acetaminophen and non‐aspirin NSAIDs on renal cell carcinoma risk. The authors analyzed data from a case‐control study and a cohort study, as well as a meta‐analytic review. Findings for aspirin and NSAIDs use were null; but, acetaminophen use was associated with increased RCC risk.